2008
DOI: 10.1029/2007ja012993
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high‐latitude ionospheric electric field variability on global thermospheric Joule heating and mechanical energy transfer rate

Abstract: [1] Effects of high-latitude ionospheric electric field variability on the Joule heating and mechanical energy transfer rate are investigated by incorporating realistic spatial and temporal characteristics of electric field variability derived from observations into the forcing of a thermosphere ionosphere electrodynamic general circulation model. First, the characteristics of subgrid-scale variability are examined from a spectral analysis of Dynamic Explorer-2 (DE-2) plasma drift measurements. The analysis re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
109
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(121 citation statements)
references
References 44 publications
6
109
1
Order By: Relevance
“…Some researchers have pointed out the importance of the electric field fluctuations for an estimation of the Joule heating rate in the thermosphere (e.g., Codrescu et al, 1995;Matsuo et al, 2003;Matsuo and Richmond, 2008;Deng et al, 2009). Deng et al (2009) estimated the altitudeintegrated Joule heating, taking into account the electric field variability.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers have pointed out the importance of the electric field fluctuations for an estimation of the Joule heating rate in the thermosphere (e.g., Codrescu et al, 1995;Matsuo et al, 2003;Matsuo and Richmond, 2008;Deng et al, 2009). Deng et al (2009) estimated the altitudeintegrated Joule heating, taking into account the electric field variability.…”
Section: Discussionmentioning
confidence: 99%
“…A useful focus is on understanding the energy transfer from the solar wind to the thermosphere-ionosphere system, via the magnetosphere as an intermediary. It has been shown that where the energy is deposited, as well as the quantity, has a large effect on the subsequent evolution of the T-I system (Deng & Ridley 2007;Matsuo & Richmond 2008). In the context of forecasting, energy can be viewed as a useful scalar quantity for which reasonably good quantitative estimates must be achieved to reach reasonable forecasts, and characterization must be improved if forecasts are to be improved (Verkhoglyadova et al 2016, this issue).…”
Section: Coupling Of the Thermosphere-ionosphere To Regions Above Andmentioning
confidence: 99%
“…It is generally thought that the lack of small-scale "electric field variability" will result in a considerable underprediction of total energy dissipation [Matsuo et al, 2003;Johnson and Heelis, 2005;Matsuo and Richmond, 2008;Deng et al, 2008]. The majority of such studies are theoretical and often use numerical simulations.…”
Section: Introductionmentioning
confidence: 99%